Investigating Monophyly of Typhlocybini Based on Complete Mitochondrial Genomes with Characterization and Comparative Analysis of 19 Species (Hemiptera: Cicadellidae: Typhlocybinae) - Xian Zhou; Yuejie Lei; Christopher H. Dietrich; Min Huang (Insects, 2023)
Tribes of the leafhopper subfamily Typhlocybinae have traditionally been defined based on differences in forewing and hindwing venation. Except for Typhlocybini (sensu lato), the classification of tribes is relatively stable. The monophyly of Typhlocybini needs to be examined, and the relationships among genera within Typhlocybini have not been resolved. Few mitogenome sequences representative of major lineages of Typhlocybini have been available to facilitate a comprehensive phylogenetic analysis of the tribe. In this study, the complete mitogenomes of 19 species of Typhlocybini were sequenced. The gene arrangements of the 19 new mitogenomes are consistent with ancestral insect mitogenomes. Phylogenetic analyses by both maximum-likelihood and Bayesian methods of 67 species of Typhlocybinae suggest that Zyginellini is paraphyletic with respect to Typhlocybini. The phylogenetic relationships within Typhlocybini are discussed, and the major results show that the Farynala and Linnavuoriana complexes previously recognized based on morphological characters correspond to monophyletic lineages.